Adaptive Behavior of Dynamic Orthoester Cryptands - Shyshov, Oleksandr; Brachvogel, Rene-Chris; Bachmann, Tobias; Srikantharajah, Rubitha; Segets, Doris; Hampel, Frank; Puchta, Ralph; Von Delius, Max (Angewandte Chemie International Edition, 2017)
The integration of dynamic covalent bonds into macrocycles has been a tremendously successful strategy for investigating noncovalent interactions and identifying effective host–guest pairs. While numerous studies have focused on the dynamic responses of macrocycles and larger cages to various guests, the corresponding constitutionally dynamic chemistry of cryptands remains unexplored. Reported here is that cryptands based on orthoester bridgeheads offer an elegant entry to experiments in which a metal ion selects its preferred host from a dynamic mixture of competing subcomponents. In such dynamic mixtures, the alkali metal ions Li+, Na+, K+, Rb+, and Cs+ exhibit pronounced preferences for the formation of cryptands of certain sizes and donor numbers, and the selection is rationalized by DFT calculations. Reported is also the first self-assembly of a chiral orthoester cryptate and a preliminary study on the use of stereoisomers as subcomponents.
Keywords: cryptands; dynamic combinatorial chemistry; supramolecular chemistry; host–guest chemistry; NMR spectroscopy

Determination of the length and diameter of nanorods by a combination of analytical ultracentrifugation and scanning mobility particle sizer - Thajudeen, Thaseem; Walter, Johannes; Srikantharajah, Rubitha; Lübbert, Christian; Peukert, Wolfgang (Nanoscale Horizons, 2017)
A combination of orthogonal measurement techniques is utilized in this study to predict the average lengths and diameters of colloidal nanorods. Sedimentation coefficient distributions and electrical mobility distributions obtained from analytical ultracentrifugation and a scanning mobility particle sizer, respectively, are used for the hydrodynamic correlation. The method is validated theoretically and application to Au and ZnO nanorod samples is shown. The results demonstrate that the combination of both measurement techniques is an excellent method for the two-dimensional characterization of nanorods.

From evaporation-induced self-assembly to shear-induced alignment - Srikantharajah, Rubitha; Schindler, Torben; Landwehr, Inga; Romeis, Stefan; Unruh, Tobias; Peukert, Wolfgang (Nanoscale, 2016)
The functionality of compact nanostructured thin films depends critically on the degree of order and hence on the underlying ordering mechanisms during film formation. For dip coating of rigid nanorods the counteracting mechanisms, evaporation-induced self-assembly (EISA) and shear-induced alignment (SIA) have recently been identified as competing ordering mechanisms. Here, we show how to achieve highly ordered and homogeneous thin films by controlling EISA and SIA in dip coating. Therefore we identify the influences of the process parameters including temperature, initial volume fraction and nanorod aspect ratio on evaporation-induced convective flow and externally applied shear forces and evaluate the resulting films. The impact of evaporation and shear can be distinguished by analysing film thickness, surface order and bulk order by careful in situ SAXS, Raman and SEM-based image analysis. For the first time we derive processing guidelines for the controlled application of EISA and SIA towards highly ordered thin nematic films.

Individualization and Stabilization of Zinc Oxide Nanorods by Covalent Functionalization with Positively Charged Catechol Derivatives - Burger, Alexandra; Srikantharajah, Rubitha; Peukert, Wolfgang; Hirsch, Andreas (Chemistry - A European Journal, 2017)
We present the formation of individualized and stabilized zinc oxide (ZnO) nanorods by functionalization with positively charged catechol derivatives by means of ligand exchange reactions. The electrosteric stabilization of ZnO nanorods was studied using two catechol derivatives, introducing either three(1) or six(2) pH independent positive charges per molecule and sterically demanding groups onto the surface. ZnO nanorods providing initially acetate (Ac) or 2-[2-(2-methoxyethoxy)-ethoxy]acetic acid (TODA) ligands on their surface were used. The ligand exchange was performed by using mono and mixed functionalization approaches, utilizing either exclusively the positively charged catechols or mixtures of the latter with small commercially available catechol derivatives, namely 4-methylcatechol (Me-cat), 4-tert-butylcatechol (tBu-cat), and dopamine hydrochloride (Dop). Using a combination of various analytical methods such as zeta potential, dynamic light scattering (DLS), UV/Vis, and scanning electron microscopy (SEM) measurements we found that the initial surfactants on the nanorods surface, the number of positive charges per molecule, the steric demand, and the added amount of the catechol derivative strongly influence the colloidal behavior of the nanorods. Stable suspensions containing individualized ZnO nanorods were successfully formed upon functionalization of ZnO-TODA nanorods with 30monolayers (MLs) of the higher charged catechol (2), as well as using mixtures of 20/10 and 18/10MLs of 2/Dop.
Keywords: catechol; colloidal sabilization; ligand exchange; surface functionalization; ZnO nanorods

Microflow-based control of near-wall fluctuations for large viscous drag reduction - Jovanovic, Jovan; Srikantharajah, Rubitha; Lienhart, Hermann; Delgado, Antonio; Frohnapfel, Bettina; Jovanović, Djordje (Microfluidics and Nanofluidics, 2011)
The stabilizing effect of microgroove surface morphology on viscous drag reduction was studied experimentally in the inlet region of a plane channel flow. The stabilization is thought to be due to the ability of a microgrooved surface pattern to suppress the velocity fluctuations in the spanwise direction on a restricted portion of the wetted surface, which prevents vorticity development at the wall and consequently across the entire flow field. This smart microflow control strategy, which works successfully only under very particular circumstances, was implemented in a microgroove-modified channel flow in which the front part has a microgrooved surface topology. The results of pressure drop measurements indicate that microgrooved surfaces can effectively stabilize laminar boundary layer development, leading to a significant reduction in the viscous drag. In the rear flat part of the microgroove-modified channel test section, a maximum drag reduction of DR ≃ 35% was measured. This corresponds to an overall drag reduction of DR ≃ 16% at a length Reynolds number of Re x ≃ 10 6: The drag reduction effect persisted in a narrow range of flow velocities and for the reported experimental conditions corresponds to microgroove dimensions between 1.5 and 2.5 viscous length-scales. © Springer-Verlag 2011.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.microf
Keywords: microflow; drag; control

Polarized Raman scattering and SEM combined full characterization of self-assembled nematic thin films - Srikantharajah, Rubitha; Gerstner, Karin; Romeis, Stefan; Peukert, Wolfgang (Nanoscale, 2016)
Elongated particles are predestined for a fast transfer of optical and electronical signals in a preferred direction, which is mandatory for a quick response in optoelectronic devices. The performance of the material is based on the quality of defect less alignment of the particles. On this account we present an easy non-invasive methodology for characterization of both surface and bulk order. The characterization of bulk order is performed by orientation dependent variation of the polarized Raman scattering signal on large areas by mapping. Scanning electron microscopy and image analysis on the surface complete the characterization. New insights in dip coated nematic structures clearly show the interplay of evaporation induced and shear-induced self-assembly and reveal a comprehensive mechanistic picture for nanorod assembly: the shear force dominated regime orients the particle in direction of withdrawal. At low withdrawal velocity, however, shear forces and evaporation counteract to produce a three-layered film where the top and bottom layers are oriented perpendicular to each other. The middle layer gives a clear evidence for a reorientation by convective flow.

Self-alignment of zinc oxide nanorods into a 3D-smectic phase - Schäfer, Stefan; Srikantharajah, Rubitha; Klaumünzer, Martin; Lobaz, Volodymyr; Voigt, Michael; Peukert, Wolfgang (Thin Solid Films, 2014)
We focus on thin films from ZnO nanorod dispersions in order to generate a high lateral order and a dense space filling structure applicable e. g. in printed optoelectronic devices. Highly stable dispersions with a solid content of up to 60 wt.% in ethanol were prepared using trioxadecanoic acid as stabilizer. With the dispersions we prepared thin films on substrates with a 3D-smectic phase in lateral dimension of cm2 and thicknesses from below 100 nm up to 1 μm. We show how the concentration of the initial solid content is influencing the formation of domains in our films and discuss the self-assembly process into ordered structures.

Surface functionalization and electronic interactions of ZnO nanorods with a porphyrin derivative - Klaumünzer, Martin; Kahnt, Axel; Burger, Alexandra; Mackovic, Mirza; Muenzel, Corinna; Srikantharajah, Rubitha; Spiecker, Erdmann; Hirsch, Andreas; Peukert, Wolfgang; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2014)
To optimize electron transfer and optoelectronic properties in nanoparticulate thin films for electronics we show the surface functionalization of ZnO nanorods by means of replacing surface active 2-[2-(2-methoxyethoxy) ethoxy]acetic acid (TODA) by a redoxactive organic component, that is, 5,10,15,20-(phenoxyacetat)-porphyrin bearing four carboxylic acids as possible ZnO anchors. Microscopy-transmission electron microscopy-And spectroscopy-optical spectroscopy-verifies the successful and homogenous integration of the porphyrin onto the surface of ZnO nanorods, a process that is facilitated by the four anchoring groups. Photophysical investigations based on emission and absorption spectroscopy prompt to distinct electronic interactions between ZnO nanorods and the porphyrins. Consequently, we performed further photophysical studies flanked by pulse radiolysis assays to corroborate the nature of the electronic interactions. © 2014 American Chemical Society.

Synergy of Catechol-Functionalized Zinc Oxide Nanorods and Porphyrins in Layer-by-Layer Assemblies - Burger, Alexandra; Kunzmann, Andreas; Costa, Ruben Dario; Srikantharajah, Rubitha; Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Catechol-functionalized, positively charged ZnO nanorods (NRs) and anionic porphyrins were integrated into layer-by-layer (LbL) assemblies. In general, this study focuses on the impact that different porphyrins, varying in size and number of negative charges, exert on the LbL architecture in terms of morphology and spectroscopy. In particular, through a combination of analytical methods, including UV/Vis spectroscopy, SEM, and profilometry, valuable insights into LbL assembly formation were gathered. A key feature was the surface coverage in the resulting films. Denser films and surface coverages were realized when highly negatively charged and sterically demanding porphyrins were employed. As a complement to basic characterization, the LbL assembled films were used to fabricate proof-of-concept solar cells.
Keywords: porphyrins; solar energy conversion; layer-by-layer assemblies; layered compounds; thin films; ZnO nanorods